The association between adrenal adenoma size, autonomous cortisol secretion and metabolic derangements. (7th December 2021) - Bleier, Jonathan; Pickovsky, Jana; Apter, Sara; Fishman, Boris; Dotan, Zohar; Tirosh, Amir; Shlomai, Gadi
Abstract: Objective: Autonomous cortisol secretion (ACS) is common in patients with adrenal incidentalomas (AI). ACS is associated with increased cardiovascular morbidity and mortality. Data regarding the association between radiological characteristics of adrenal adenomas, their hormonal functionality and metabolic outcomes, are scarce and inconclusive. In this study, we aim to delineate the association between radiological characteristics of AI, ACS and metabolic status. Methods: A cross‐sectional study of 77 patients with AI who underwent a comprehensive hormonal evaluation. Radiological assessments were performed by an independent radiologist blinded to the clinical and hormonal phenotype of each case. Linear regression models were used to evaluate the association between post dexamethasone suppression test (DST) cortisol levels, metabolic indices and radiological measurements. Results: Mean maximal adenoma diameter was greater in patients with versus without ACS (20.35 ± 6 vs. 27.09 ± 9.3 mm, respectively, p  < .01). Maximal adenoma diameter was found to be positively and linearly correlated with post‐DST morning cortisol levels across their entire range ( R  = .474, p  < .01). Linear correlations between maximal adenoma diameter and indices of glycemic control showed a correlation coefficient ( R ) of .481 and .463 for fasting plasma glucose (FPG) and haemoglobin A1c (HbA1c), respectively, p  < .01. When analysis included only patients with ACS, an R  = .584 and R  = .565 was observed for FPG and HbA1c, respectively ( p  < .01 for both). The association between maximal adenoma diameter and both FPG and post‐DST morning cortisol intensified in patients with metabolic syndrome. Conclusion: There is a quantitative positive mild correlation between AI size and both cortisol autonomy and metabolic parameters.